Silvicultural treatments improve pest and disease conditions of white pine (Pinus strobus) residual trees and regeneration - Munck, Isabel Alvarez; Yamasaki, Mariko; Janelle, Jon (Frontiers in Forests and Global Change, 2023)
Managing multiple forest insect pests and diseases is challenging. For example, in eastern white pine (Pinus strobus) stands whereas partial shading and high seedling density is encouraged to reduce damage by white pine blister rust (Cronartium ribicola) and white pine weevil (Pissodes strobi), dense conditions in the understory may increase damage by foliar diseases such as brown spot needle blight (Lecanosticta acicola) and Caliciopsis canker (Caliciopsis pinea). We evaluated the effect of silvicultural treatments, shelterwoods (residual basal area < 18 m2 ha−1), low density thinnings (residual basal area ≤ 14 m2 ha−1), patch cuts (1.2 ha openings), and untreated controls on damage by these insect pest and diseases in residual overstory trees and regeneration. Shelterwoods and low density thinnings provided a good balance of some shading and reduced stem density, which resulted in less weevil damage and foliar disease severity. Crown condition and quality of regeneration was better in all treatments compared to unmanaged controls. Shelterwoods, low density thinnings and patch cuts have the added benefit on increasing seral habitat, resulting in greater songbird diversity.